FUNGSI LEMBAGA OMBUDSMAN DALAM PENGAWASAN PENYELENGGARAAN PELAYANAN PUBLIK PADA BIDANG PENDIDIKAN DI KOTA SURABAYA - Faizun, Atik Nur (JPAP: Jurnal Penelitian Administrasi Publik, 2017)
This study aims to determine the function of the Ombudsman Institution Supervision of Public Services In The Field Education in Surabaya and to determine the follow-up of the Ombudsman of the Republic of Indonesia in an effort to improve public services in education in the city of Surabaya. Data qualitative research is then presented descriptively, that is to parse, explain and illustrate in accordance with the problems linked to this research. The research was conducted in the Office of the Ombudsman of the Republic of Indonesia East Java province to interview Chief Ombudsman of the Republic of Indonesia Representatives of East Java, and Assistant Ombudsman of the Republic of Indonesia Representatives of East Java. The results showed that the existence of the Ombudsman in Indonesia has been regulated through the provisions of Law No. 37 of 2008 on the Ombudsman of the Republic of Indonesia, which was previously the existence of the Ombudsman has been in Presidential Decree No. 44 of 2000, but seems still very vague. Many things are not regulated in detail and firm, it is different with Law Number 37 Year 2008, in the Act No. 37 of 2008 what became the object of scrutiny Ombudsman highly emphasized and detailed mentioned. While the regulations governing oversight bodies that exist, it appears the position and function of the Ombudsman as an institution is not the same supervision by institutions other oversight, both external and internal. The function of the Ombudsman In Control of Public Services In The Field Of Education In Surabaya forms that do (1) prevention of maladministration in the field of education in the form of community empowerment through a form of socialization, talk shows, interactive dialogue, gatherings, lectures and others as well as activities Investigation. (2) the handling of complaints in the field of education through the investigation, clarification, mediation, and monitoring. And Procedures for Examination and Completion Report Ombudsman Republic of Indonesia in an effort to improve public services in education in the city of Surabaya in accordance with Law No. 37 of 2008 on the Ombudsman of the Republic of Indonesia. Â  Keywords : Public Services, Oversight, Ombudsman.